Effectiveness of Deworming with Single-Dose Albendazole for Preschool-Aged Children in the Dominican Republic. (March 2021) - Japa, Ingrid; Ancha, Bhavya; Custodio, Antonio; Ohrenschall, Rachel; Cordero, Ramona; Deverlis, Adriana; Chapman, Jennifer; Hickson, Meredith R.; Steenhoff, Andrew P.; Lowenthal, Elizabeth D.
Background . The World Health Organization recommends biannual deworming with single-dose albendazole for all children over 1 year in regions where soil-transmitted helminths (STH) are endemic. There are limited data from the Dominican Republic (DR) on the effectiveness of deworming programs. Methods . Between January and June 2019, we enrolled 63 preschool-aged children at a community clinic in the DR. Participants received albendazole at enrollment. Stool samples were collected and examined for parasites at enrollment, 2 to 4 and 12 to 16 weeks post-albendazole. Caregivers were surveyed on home hygiene practices and children's symptoms. Findings . At enrollment, 1 or more parasites were noted in 89% of samples. Ascaris lumbricoides (68%) was the most common species, followed by Entamoeba histolytica (35%) and Giardia intestinalis (8%). Two-to-four weeks post-albendazole, fewer than half of those with A. lumbricoides infections at baseline had cleared the infection. STH symptoms significantly improved between enrollment and 2 to 4 weeks. By 12 to 16 weeks after treatment, A. lumbricoides infections were as high as baseline. Interpretation . Although limited by size and available technology, our study contributes data on STH in the DR. Single-dose deworming with albendazole did not reduce Ascaris lumbricoides infections in our sample. As STH are the most common neglected tropical diseases and negatively impact children's health globally, further studies on both effective deworming programs and interventions to prevent STH are needed.